Lead exposure was associated with liver fibrosis in subjects without known chronic liver disease: An analysis of NHANES 2017–2020 - Zhang, Zhiqiang; Li, Zhangping; Lin, Haiyan; Zeng, Zhiyu; Huang, Jiaofeng; Li, Dongliang (Frontiers in Environmental Science, 2022)
Lead is one of the most important toxic heavy metals in the environment; however, the relationship between blood lead levels and liver fibrosis in individuals without chronic liver diseases (CLD) is unclear. This study used data obtained from the National Health and Nutrition Examination Survey (NHANES) 2017–2020. Multivariate logistic regression was used to explore the relationship between the blood lead level and significant liver fibrosis. A total of 1962 cases without underlying CLD were included, 77 (3.9%) of whom were diagnosed with advanced liver fibrosis by transient elastography. The proportion of advanced fibrosis significantly increased with the blood lead level (P<0.001), and the blood lead level was higher in the fibrosis group than in the non-fibrosis group (1.2 μg/dL vs. 0.9 μg/dL, P<0.001). After adjusting for relevant confounding factors, the blood lead level was found to be independently associated with advanced liver fibrosis (OR=1.168; 95% CI, 1.006–1.356; P=0.041). The blood lead level remained an independent risk factor for advanced liver fibrosis (OR=1.249; 95% CI, 1.048–1.489; P=0.013) after controlling for age and sex through propensity score matching. In conclusion, the blood lead level is associated with liver fibrosis in individuals without known CLD.